2013
DOI: 10.1074/jbc.m113.463653
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Core-2 GlcNAc-transferase and ST6GalNAc-transferase Regulates the Synthesis of the Leukocyte Selectin Ligand on Human P-selectin Glycoprotein Ligand-1

Abstract: Background: Carbohydrate epitopes at the N terminus of PSGL-1 (P-selectin glycoprotein ligand-1) facilitate leukocyte binding to selectins. Results: O-linked glycan microheterogeneity analysis at the PSGL-1 N terminus demonstrates the presence of both the core-2 sialyl Lewis-X (sLe X ) and di-sialylated T-antigen. Conclusion: Overexpression of ST6GalNAc-transferases reduced both sLe X expression and selectin-mediated leukocyte adhesion. Significance: ST6GalNAc2 is a novel enzyme that regulates leukocyte adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 50 publications
1
43
0
1
Order By: Relevance
“…The selectins bind a variety of carbohydrate epitopes on the leukocyte cell surface, with the sialyl Lewis-X (sLe X ) glycan representing the prototypic selectin-ligand 4 , 6 , 7 . This is a sialofucosylated tetrasaccharide (Neu5Acα2,3Galβ1,4[Fucα1,3]GlcNAc) containing an α(2,3)-linked sialic acid and α(1,3)-linked fucose.…”
Section: Role Of Carbohydrates In the Leukocyte Adhesion Cascadementioning
confidence: 99%
See 1 more Smart Citation
“…The selectins bind a variety of carbohydrate epitopes on the leukocyte cell surface, with the sialyl Lewis-X (sLe X ) glycan representing the prototypic selectin-ligand 4 , 6 , 7 . This is a sialofucosylated tetrasaccharide (Neu5Acα2,3Galβ1,4[Fucα1,3]GlcNAc) containing an α(2,3)-linked sialic acid and α(1,3)-linked fucose.…”
Section: Role Of Carbohydrates In the Leukocyte Adhesion Cascadementioning
confidence: 99%
“…Further, in order to enhance its accessibility to the selectins, PSGL-1 is localized at the tips of the leukocyte microvilli 14 . While there is a heterogeneous distribution of O-glycans at T57, the functional selectin-ligand at this site is a non-extended sialyl Lewis-X glycan contained within a core-2 motif 7 (Fig. 2).…”
Section: Futs Regulating P- and L-selectin Binding Are Similar In Hummentioning
confidence: 99%
“…The binding in these experiments was abrogated by an anti-E-selectin mAb HAE-1f ( Figure 3A-C). The antihuman (KPL-1, Figure 3A-B) and murine PSGL-1 mAbs (2PH1, Figure 3C) had a minor effect, 35,36 possibly due to the inhibition of secondary leukocyte-leukocyte capture in addition to primary leukocyte recruitment onto the substrate.…”
Section: Blood 22 January 2015 X Volume 125 Number 4 Regulation Of mentioning
confidence: 99%
“…Regulation of human myeloid cell binding to P-and L-selectin A core 2-based O-linked glycan bearing the sLe X epitope, located at the N terminus of PSGL-1, at Thr-57 in humans, 35,39 is the primary ligand for L-and P-selectin. Studies with knockout mice show that the biosynthesis of this O-glycan is initiated by the formation of the core 1 structure (Galb1,3GalNAca1-Thr) catalyzed by the core-1 b1,3galactosyltransferase/T-synthase.…”
Section: Application Of Crispr/cas9 For Studies Of Leukocyte Functionmentioning
confidence: 99%
“…Such studies have demonstrated that the sialyl Lewis-X (sLe X ) tetrasaccharide attached to a core-2 O-glycan at the N-terminus of P-selectin glycoprotein ligand-1 (PSGL-1, CD162) is a major ligand for P- and L-selectin in both humans and mice 7-9 . Whereas only 2% of the overall O-glycans of human PSGL-1 contain the sLe X core-2 O-glycan 10 , in myeloid cells, this structure constitutes ~20% of the carbohydrates at Thr-57 on the N-terminus of this glycoprotein 11 . With regard to E-selectin, the physiological carbohydrate ligands likely differ between mice and humans 1, 3 .…”
Section: Introductionmentioning
confidence: 99%